2020
DOI: 10.1016/j.ptsp.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of injuries in adult amateur rowers: A cross-sectional study

Abstract: Main outcome measures: Frequency, type, location, severity and associated rowing-related factors associated with injury.Results: Injury rate was 5.7 per 1000 sessions, with no effect of sex (χ 2 = 0.195, P = 0.659) or weight class (χ 2 = 0.800, P = 0.371). The lower-back demonstrated an epidemiological incidence proportion (IP) of 0.39 (95% CI = 0.33 to 0.46). The IP for water-and land-based training was 0.39 (95% CI = 0.31 to 0.47) and 0.57 (95% CI = 0.49 to 0.65), respectively. IP was highest between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…[5] These findings may be attributed to the comprehensive health management of elite athletes through resources and support. [13] Amateur athletes may not have the same level of medical care readily available and therefore experience a different approach to injury compared to those athletes of a higher level. [13] This study's combined sample (n=87) reported an average ADI disability of 24.7%±18.1%, which is classified as a moderate disability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5] These findings may be attributed to the comprehensive health management of elite athletes through resources and support. [13] Amateur athletes may not have the same level of medical care readily available and therefore experience a different approach to injury compared to those athletes of a higher level. [13] This study's combined sample (n=87) reported an average ADI disability of 24.7%±18.1%, which is classified as a moderate disability.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Amateur athletes may not have the same level of medical care readily available and therefore experience a different approach to injury compared to those athletes of a higher level. [13] This study's combined sample (n=87) reported an average ADI disability of 24.7%±18.1%, which is classified as a moderate disability. [10] These findings corresponded with previous studies which similarly reported a moderate severity of LBP in university rowers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence of LBP was reported as 1.5-3.7 per 1000 hours of rowing training and competition, 21,23,24 and LBP prevalence was observed to be between 6% and 66% over 12 months. 8,21 Seventeen papers reported incidence, 8,20,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] the number of people developing LBP during one time, while nine papers reported prevalence, 3,22,23,27,[38][39][40][41][42] the number of people who have LBP at one time. Three papers employed a prospective design with both incidence and prevalence reported.…”
Section: Total 6 (8)mentioning
confidence: 99%